Toxicity and relative selectivity of acephate to target and non-target organisms - Mohamad, Rosli; Oloffs, Peter C. (Universiti Putra Malaysia Press, 1987)
Aspects of toxicity and activity of acephate were studied in non-diapausing, laboratory-bred larvae of Choristoneura occidentalis Freeman, larvae of Anagasta kuehneilla (Zeller), and in male Wistar rats. Inhibition of human erythrocyte acetylcholinesterase (AChE) in vitro was also investigated. Topically applied acephate was twice as toxic to last-instar larvae of C. occidentalis as to last-instar larvae of A. kuehniella. However, it was less toxic to C. occidentalis larvae than methamidophos or paraxon. These results were supported by a series of in-vitro experiments in which anti-AChE activity decreased in the order: paraoxon methamidophos acephate. There was indication that acephate per se inhibits AChE in vitro in proportion to its toxicity in vivo.